Culturally authentic tasks: perceptions among Indian teachers teaching english in tamil schools - Kannan, Rajendran (2007)
Culture and language have been part and parcel of human life since ages. Everyday culture and language play an important role in shaping thoughts and ideas in our everyday lives. In fact language is culture. For the same argument, language learning and culture are inseparable as culture facilitates both the learning and teaching of language. This study has been undertaken to gather perceptions among the Indian teachers who teach English in Tamil schools towards culturally authentic tasks. In addition, the research seeks to find out the considerations for effective culturally authentic tasks as perceived by the teachers. The findings suggest that teachers perceived culture as a critical tool in language teaching especially in designing culturally based materials. Besides, the teachers considered cultural materials for language learning and teaching as very effective because such materials assist both the teacher and learners in the classroom. The insights from this research will hopefully enlighten the curriculum planners and syllabus and material designers on the importance of culturally based concepts in the English language syllabus.